2008
DOI: 10.1270/jsbbs.58.309
|View full text |Cite
|
Sign up to set email alerts
|

Development of a locus-specific marker and localization of the Rysto gene based on linkage to a catalase gene on chromosome XII in the tetraploid potato genome

Abstract: As a result of many decades of potato breeding in Keszthely, Hungary, numerous varieties resistant to the pathogens attacking potato have been developed using wild Solanum species as resistance sources. In order to simplify the time-consuming breeding process, the present research project involved the development of a SCAR marker correlating with the Ry sto gene, originating from the Solanum stoloniferun species and conferring extreme resistance to the potato Y virus (PVY), using sequence information from a RA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…This is because both CDDP and IT use primers based on allele sequences of functionally characterised genes, and thus specific banding patterns corresponding to plant phenotypes can be identified. In a previous study using IT markers, Cernák et al (2008) showed that a portion of the catalase gene is linked to Potato virus Y (PVY) resistance and that this gene might play a role in extreme defense mechanisms in solanaceous plants. However, the development of such markers depends on the availability of robust genomic databases.…”
Section: Discussionmentioning
confidence: 99%
“…This is because both CDDP and IT use primers based on allele sequences of functionally characterised genes, and thus specific banding patterns corresponding to plant phenotypes can be identified. In a previous study using IT markers, Cernák et al (2008) showed that a portion of the catalase gene is linked to Potato virus Y (PVY) resistance and that this gene might play a role in extreme defense mechanisms in solanaceous plants. However, the development of such markers depends on the availability of robust genomic databases.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular markers co-segregating with Ry sto , e.g., STM0003, YES3-3A, Cat-in2 and ST1, were identified earlier [16,31-33,40]. The closest markers to Ry sto in the genetic map of ‘White Lady’ were STM0003 and ST1 in a distance of 2.95 and 0.53 cM, respectively [31].…”
Section: Resultsmentioning
confidence: 99%
“…andigena ( Ry adg ) and was mapped on chromosome XI [12]. Another one, derived from S. chacoense ( Ry chc ), is located on chromosome IX [13], while the third one, derived from S. stoloniferum ( Ry sto ), was mapped to chromosome XII [1416]. A gene, designated Y-1 , co-segregating with Ry adg , was cloned and found to be structurally similar to gene N that confers HR to Tobacco mosaic virus (TMV) in Nicotiana spp.…”
Section: Introductionmentioning
confidence: 99%
“…One of them is originated from the wild species S. stoloniferum (gene Ry sto ) and mapped to chromosome XII (Flis et al, 2005;Song et al, 2005;Cernák et al, 2008). Although the Ry sto gene has not been identified yet, it is very probable that, as the majority of characterised viral resistance genes from plants, it belongs to the NBS-LRR class of resistance genes (Gururani et al, 2012).…”
Section: Genes Associated With Er Type Resistancementioning
confidence: 99%